Vamplets: Nightmare Nursery 03 - Middleton, Gayle; Dwonch, Dave (Action Lab Entertainment, 2015)
Enter the Secret Society of the Poison Black Apple. Destiny Harper is in deep trouble, and she will need the help of Rasket, Lycinda and the Vamplets themselves to thwart the plans of the evil Vammette. Will Destiny Harper get back home, or will she be trapped on the nightmare world of Gloomvania forever?